Measuring bonding or attachment in the parent-infant-relationship: A systematic review of parent-report assessment measures, their psychometric properties and clinical utility. (December 2020) - Wittkowski, A.; Vatter, S.; Muhinyi, A.; Garrett, C.; Henderson, M.
Abstract: Background: Meaningful, valid and reliable self-report measures can facilitate the identification of important parent-infant-relationship factors, relevant intervention development and subsequent evaluation in community and clinical contexts. We aimed at identifying all available parent-report measures of the parent-infant-relationship or bond and to appraise their psychometric and clinimetric properties. Method: A systematic review (PROSPERO: CRD42017078512) was conducted using the, 2018 COSMIN criteria. Eight electronic databases were searched. Papers describing the development of self-report measures of the parent-infant-bond, attachment or relationship from pregnancy until two years postpartum or the assessment of their psychometric properties were included. Results: Sixty-five articles evaluating 17 original measures and 13 modified versions were identified and reviewed. The studies' methodological quality (risk of bias) varied between 'very good' and 'inadequate' depending on the measurement property assessed; however, scale development studies were mostly of 'inadequate' quality. Although most measures had good clinical utility, the psychometric evaluation of their properties was largely poor. The original or modified versions of the Postpartum Bonding Questionnaire collectively received the strongest psychometric evaluation ratings with high quality of evidence. Conclusions: This novel review revealed that only a few antenatal and postnatal measures demonstrated adequate psychometric properties. Further studies are needed to determine the most robust perinatal measures for researchers and clinicians. Highlights: Parental perceptions of the parent-infant-bond are important in identifying any difficulties and strengths. This is the first comprehensive review to assess the psychometric properties of 14 antenatal and 18 postnatal measures. The Postpartum Bonding Questionnaire was the most researched measure compared to other measures. The administrative properties were good for most measures, suggesting their feasibility, acceptability and attainability. Although several studies reported on validity and reliability, most measures lacked adequate methodological quality.